2021
DOI: 10.1177/16094069211002749
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Relevance of Signs and Symptoms to Identify Exit Site Infection of a Hemodialysis Central Venous Catheter: A Delphi Study Protocol

Abstract: Vascular access is a potentially fatal vulnerability for hemodialysis patients, and a notable area for improvement for healthcare providers. Hemodialysis central venous catheters (HD-CVC) are associated with increased morbidity and mortality from infectious complications. Clinical practice guidelines on vascular access for hemodialysis and infection control do not provide a standard definition for infection of the HD-CVC exit site. The main aim of this protocol is to establish consensus on the signs and sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The rounds took place between November 2020 and March 2021. Details on the study protocol have been published elsewhere (Cobo‐Sánchez et al., 2021). The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for reporting a cross‐sectional survey (Elm et al., 2007) were used (Data S1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rounds took place between November 2020 and March 2021. Details on the study protocol have been published elsewhere (Cobo‐Sánchez et al., 2021). The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for reporting a cross‐sectional survey (Elm et al., 2007) were used (Data S1).…”
Section: Methodsmentioning
confidence: 99%
“…The research team identified a list of signs and symptoms related to ES or HD‐CVC TI from the definitions of this dimension identified in a previous literature review (Cobo‐Sánchez et al., 2023). This review included a manual review of seven relevant clinical practice guidelines on haemodialysis vascular access care and infection control, in addition to 40 documents from automated searches in different databases, identifying 25 signs/symptoms (Cobo‐Sánchez et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Delphi protocol has been published recently. 35 The prioritisation thus obtained will be used to develop the preliminary version of the assessment scale we propose. 2.…”
Section: Methods and Analysis Designmentioning
confidence: 99%
“…After identifying the clinical signs and symptoms, by a scoping review of the literature, they will be categorised by an international panel of experts in HD-CVC exit site care, using the Delphi technique. The Delphi protocol has been published recently 35. The prioritisation thus obtained will be used to develop the preliminary version of the assessment scale we propose.…”
Section: Methods and Analysismentioning
confidence: 99%